"Footnotes in Gaza". The comic-report as journalistic genre - Melero Domingo, Javier (Estudios sobre el Mensaje Periodístico, 2012)
The recent explosion of non-fiction comic has been followed by the birth of a genre characterized by current contents relate. This creative formula imports journalism codes to report facts, through sequential narrative, with a veracity objective. A circumstance which suggests a theoretical conflict against the normative tradition of journalism. This paper investigates the journalistic dimension of these products from an specific case of study: the analysis of Footnotes in Gaza. A comic that won 2010 award for investigative journalism of Fertel Foundation, and whose author, Joe Sacco, is considered one of the most respected names in this trend that hybridizes comics and journalism.